Nonlogarithmic death rate calculations for Byssochlamys fulva and other microorganisms. - King, A D (1979)
Survivor curves for heat-resistant ascospores of Byssochlamys fulva exposed to lethal heat were nonlogarithmic. At lower heating temperatures, the log survivor curves were characterized by a shoulder plus an accelerating death rate; with increased temperatures, the rate approached logarithmic death. The formula (log No -- log N)a = kt + C was adapted to linearize these data. No and N are the initial and surviving numbers of organisms at the time t. The death rate is given by k, and C is a constant for a set of data. The a value is derived from the least-squares slope of a plot of log (log No -- log N) against log time and is used to linearize the thermal death rate curves. This formula permitted calculations of parameters analogous to those for logarithmic death (D and z). Use of formula is illustrated for selected nonlinear microbial death rate curves from the literature.